Europe's silicon star rises. - Geppert, L.
Despite recent worldwide economic turmoil, Europe holds a strong hand in semiconductor chips for communications and industrial applications. Now Belgium and Scotland, relative newcomers to the industry, are upping the ante with bold new ventures that could bring even more business into the region. The author discusses these new ventures
Keywords: Belgium; Europe; Scotland; Communications; Industrial applications; Semiconductor chips manufacture